Land Execution as Collateral in Debt Agreement Default: A Case Study of Decision No. 65/PDT.BTH/2022/PN KDI - Devinny, Kelly; Agustining, Agustining; Azharuddin, Azharuddin; Rivai, Yasdan (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the implementation of land execution as collateral in a debt agreement when the debtor is in default, using the Kendari District Court Decision Number 65/Pdt.Bth/2022/PN Kdi as a case study. The background of this study stems from the persistent legal disputes between creditors and debtors regarding the mechanism for executing collateral objects in the form of land, particularly when the agreement lacks a valid material guarantee or violates the principles of contract law. The research adopts a normative juridical approach by examining relevant legal provisions, including the Civil Code, Law No. 4 of 1996 concerning Mortgage Rights, as well as doctrines and jurisprudence related to collateral execution. In addition, an empirical juridical approach was employed to evaluate the practical application of these legal norms in the Kendari District Court. Data were collected through literature review, decision analysis, and interviews with parties familiar with the case. The findings indicate that the execution of land as collateral for debt in this case was conducted through a request for an execution order after the debtor was proven to be in default. However, the process encountered obstacles due to the absence of a valid mortgage deed as the legal basis for execution. The judge, in rendering the decision, upheld the principles of justice and legal certainty by rejecting the execution request and emphasizing that a debt agreement not accompanied by a valid mortgage deed cannot serve as the legal foundation for executing the land object.